PENGARUH LITERASI KEUANGAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN MAHASISWA BISNIS DAN NON BISNIS - Nurniah; Eka Astra Susilawaty , (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Financial literacy is a combination of the awareness, knowledge, skills, attitudes and behaviors that a person needs to have to make sound financial decisions and ultimately achieve individual financial well-being. The purpose of this research is to know the description of financial literacy and financial management behavior on students, and to find out the effect of financial literacy on student financial management. The objects in this study were 201 Business student Group and 254 from non business student group State polytechnic of Ujung Pandang. The results of data collection through a questionnaire are then processed and analyzed with the linear simple regression statistical method. Based on the results obtained that financial literacy with indicators of basic knowledge of personal finance, savings and loans, insurance and investment shows that affect the financial management of students both business and non business students.